Australasian bronchiolitis guideline. (15th July 2018) - O'Brien, Sharon; Borland, Meredith L; Cotterell, Elizabeth; Armstrong, David; Babl, Franz; Bauert, Paul; Brabyn, Christine; Garside, Lydia; Haskell, Libby; Levitt, David; McKay, Nicola; Neutze, Jocelyn; et al.
Abstract : Aim: Bronchiolitis is the most common lower respiratory tract disorder in infants aged less than 12 months, and research has demonstrated that there is substantial variation in practice patterns despite treatment being well defined. In order to align and improve the consistency of the management of bronchiolitis, an evidence‐based guideline was developed for the Australasian population. Methods: The guideline development committee included representation from emergency and paediatric specialty medical and nursing personnel in addition to geographical representation across Australia and New Zealand – rural, remote and metropolitan. Formulation of the guideline included identification of population, intervention, comparator, outcomes and time questions and was associated with an extensive literature search from 2000 to 2015. Evidence was summarised and graded using the National Health and Medical Research Council and Grading of Recommendations Assessment, Development and Evaluation methodology, and consensus within the guideline group was sought using nominal group technique principles to formulate the clinical practice recommendations. The guideline was reviewed and endorsed by key paediatric health bodies. Results: The guideline consists of a usable clinical interface for bedside functionality supported by evidence summary and tables. The Grading of Recommendations Assessment, Development and Evaluation and National Health and Medical Research Council processes provided a systematic and transparent process to review and assess the literature, resulting in a guideline that is relevant to the management of bronchiolitis in the Australasian setting. Conclusion: This is the first robust Australasian acute paediatric guideline and provides clear guidance for the management of the vast majority of patients seen in Australasian emergency departments and general paediatric wards with bronchiolitis.